Recurrence patterns in patients with advanced non-small cell lung cancer who have received epidermal growth factor receptor tyrosine kinase inhibitors - Zhuang, Mengqi; Chen, Zheng; Li, Jing; Dai, Honghai; Zhuang, Cheng; Yang, Zhe; Han, Junqing (European Journal of Oncology and Environmental Health, 2016)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs), such as gefitinib and erotinib, have shown efficacy in patients with advanced non-small cell lung cancer (NSCLC). However, information on initial failure sites in patients treated with EGFR-TKIs is limited. This retrospective study was undertaken to investigate the recurrence patterns in these patients. We retrospectively reviewed the initial failure sites of 52 EGFR-TKI treated patients with stage III/IV NSCLC and sensitizing EGFR mutation in Shandong Provincial Hospital. The median progression free survival (PFS) was evaluated by the Kaplan-Meier method. The median age of the 52 patients treated with EGFR-TKIs was 57 years (range, 37-80 years). The median PFS was 8 months. The most frequent initial site of progression was the lung (38.46%), which was followed by the central nervous system (CNS) (30.77%), bone (17.31%) and other places (liver, adrenal, skin, etc.). The lung and CNS were two of the most common recurrence sites in EGFR-TKI treated patients with stage IIIB/IV NSCLC harboring somatic EGFR mutation. We should pay more attention to the response of the lung and brain for early detection of disease recurrence.